The Sedimentary Record of Paleogene Sequences in Sarawak, Malaysia - Franz L. Kessler; John Jong; Mazlan Madon (Ikatan Ahli Geologi Indonesia, 2021)
In this paper, we compare the oldest Tertiary sedimentary sequences in the south ern margin of the South China Sea based on outcrop and well data along the Sarawak margin, northern Borneo. Paleogene rocks in Sarawak are present in three tectono stratigraphic zones and represent three depositional settings. Outcrops and deep exploration wells in the Miri Zone indicate shelfal clastics, carbonates, and clay dominated neritic sediments. In the Sibu Zone (Rajang Fold Thrust Belt), Late Cretaceous to Late Eocene deep marine clastic sediments indicate a shallowing upward of the depositional basin, which was later buried to great depths (?) and metamorphosed. In the Kuching Zone, the Kayan and Plat eau sandstones represent a fluvial dominated non marine depositional setting. There are two major unconformities within the Paleogene of Sarawak: the Rajang Unconformity, dated as approximatively 37 Ma, and the younger near Top Eocene (a.k.a. Base Oligocen e) unconformity of 33.7 Ma. The likely presence of Eocene strata in the margins of Sundaland is associated with an early phase of regional extensional tectonism, which was also observed in the Penyu and Malay basins, offshore Peninsular Malaysia, and is probably related to the onset of rifting of the South China Sea continental crust.